Antioxidant analysis of different parts of Carica papaya - A. M., Maisarah; B., Nurul Amira; Rahmat, Asmah; Othman, Fauziah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
This study was conducted to compare the total antioxidant activity (TAA), total phenolic content (TPC) and total flavonoid content (TFC) from the different parts of papaya tree including their ripe and unripe fruit, seeds and the young leaves. Two methods namely DPPH radical scavenging activity and β-carotene bleaching assay were used to determine the TAA, whereas TPC was determined by Folin-Ciocalteu's method while TFC by aluminium trichloride (AlCl3). For these purposes, methanolic extracts (80%) were prepared. The results showed that the highest antioxidant activity through β-carotene bleaching assay was observed in unripe fruit (90.67 ± 0.29%) followed by young leave, ripe fruit and the seed. In other hand, young leaves exhibited a significant higher scavenging effect compared to others and the dose required in reducing the absorbance of DPPH control solution by 50% (EC50) was calculated at 1.0 ± 0.08mg/ml. The EC50 values were 4.3 ± 0.01mg/ml, 6.5 ± 0.01mg/ml and 7.8 ± 0.06mg/ml for unripe fruit, ripe fruit and seeds respectively. Interestingly, both TPC and TFC also showed that young leaves had the highest antioxidant content (424.89 ± 0.22mg GAE/ 100 g dry weight and 333.14 ± 1.03mg rutin equivalent/ 100 g dry weight, respectively). Statistically, Pearson correlation showed there were positive correlations between TPC and TFC with antioxidant activity assayed by DPPH radical scavenging assay (r=0.846 and r=0.873, respectively). However there was no correlation between TPC and TFC with β-carotene bleaching activity. In brief, taken into account all the parameters measured, antioxidants were highly remarkable in the sequence of young leaves > unripe fruit > ripe fruit > seed. Nevertheless, further investigation for isolation and identification of the phytoconstituents responsible for antioxidant activity is desirable.